Towards understanding the effect of work on teacher’s mental health: a mixed method study - Aziz, Rahmat; Abdullah, Irwan; Rahayu, Iin Tri; Sa'diyah, Elok Halimatus; Nashori, Fuad (International Journal of Public Health Science (IJPHS), 2024)
Working as a teacher significantly impacts mental health, both psychological well-being and psychological distress. This study examines the effect of working as a teacher on mental health. A mixed-method sequential explanatory design was chosen because it aims to test theories and provide detailed explanations for the results. Quantitative data were collected from 153 primary school teachers in East Java, and qualitative data were collected from 12 teachers who were purposively selected as interview subjects. The data were collected through interviews and four psychological scales (work commitment, engagement, job satisfaction, and mental health). Statistical inferential analysis and thematic analysis were used to analyse the data. The analyses showed that teachers’ jobs affected their mental health in terms of psychological well-being and psychological distress. Work commitment effected on mental health R=.653, R2=.426 p<.001; work engagements effected on mental health R=.479, R2=.230 p<.001; and job satisfaction effected on mental health R=.668, R2=.446 p<.001. The findings suggest that teachers’ mental health can be strengthened through their attitudes and behaviours towards work.